Petrotectonic framework of Siwalik Group in Khairi Murat-Kauliar area, Potwar Sub-Basin, Pakistan: DOI: 10.48129/kjs.17577 - Ali, Syed Kamran; Jahanzeb Khan; Muhammad Saleem Mughal; Muhammad Rafiq Lashari; Sahito, Ali Ghulam; Fahad Hameed; Hafiz Sohaib Bashir; Ahmer Bilal; Syed Saqib Razzaq (Kuwait Journal of Science, 2023)
The Khairi Murat-Kauliar area lies between the Salt Range Thrust (SRT) in the south whereas Main Boundary Thrust (MBT) in the north which is the part of the Potwar Sub Basin. Eocene to Recent rock succession is exposed in the study area. The selected siliciclastic Siwalik Group display various facies in a fluviatile environment, with different lithologies, and sedimentary features. The petrographic studies of Siwalik Group delineate different microfacies including feldspathic litharenite, litharenite and sub arkose. The provenance study of sandstones depicted the terrane of dissected arc and recycled orogeny, indicating that the detritus was received from sedimentary, metamorphic, plutonic and volcanic rocks from the northern domain of Indian Plate, Karakoram Ranges and Kohistan Island arc. The Siwalik sandstone also contains heavy mineral assemblage such as tourmaline, garnet, epidote, hornblende and chlorite. This heavy detritus assemblage depicted that the deposits were received from metamorphic and igneous origin. A modified dynamic depositional stages of the Siwalik Group with respect to Himalayan orogeny is further built using outcrop data, microfacies and heavy minerals analysis. According to this concept, the group was deposited along Himalayan uprising and thrusting, on the depository in targeted area. The Siwalik Group depicted different phase of Himalayan tectonics and these molasse sequence were deposited in a subsiding foreland basin under the conditions of rapid erosion and quick deposition.